Teacher's Efforts to Overcome Students Difficulties in Writing the Qur’an Verses - Arisa Natasha Wangi; Rohmatul Azizah Putri; Fuady Anwar; Rahmatul Hasni Firza; Andrian Dwi Kurniawan; Fidiatul Ayu Rizki; Gifa Oktavia (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2022)
This study aims to identify the forms of student’s difficulties in learning to write the Quran verses in the subject of Islamic Religious Education. This research uses a qualitative method with a case study approach. This research was taken through direct interviews with eight informants. Overall the research findings This shows four teacher efforts in overcoming students difficulties in writing the Quran verses, namely: i) using the alphabetic method (the letter recognition method) to make it easier for students to recognize hijaiyah letters first before writing the Quran verses, ii) using the drill method, students are taught to write pieces of the Quran verses repeatedly so that students dexterity is honed in writing, iii) Game-based Synthetic Analytical Structural methods, in this use can improve learning outcomes and the active role of students in writing and reading the Quran because it can overcome student saturation of the material Islamic Religious Education, iv) Imla’ method, this method can be used if students are already proficient in the basics of writing the Quran verses because this method emphasizes the posture of letters in the form of words or sentences of the Qur’an.